Heavy Metals Pollution and Potential Health Risks: The Case of the Koche River, Tatek Industrial Zone, Burayu, Ethiopia - Mathewos Temesgen; Tegenu Alemu; Enkosa Shasho (Journal of Toxicology)
This study aimed to determine the levels of some heavy metals in the Koche River and the potential health risks. A replica of water samples was taken from 12 sampling sites purposely selected in the dry season. Heavy metal levels were determined using a flame atomic absorption spectrophotometer following the APHA (1998) procedure. Heavy metal pollution index (HPI), heavy metal evaluation index (HEI), chronic daily intake (CDI), hazard quotient (HQ), hazard index (HI), total hazard index (THI), and incremental lifetime cancer risk were calculated on the basis of the results. The heavy metals detected were Fe > Mn > Cu > Zn > Cr. The Cr, Fe, Mn, and Cu contents were above the maximum allowed limit of WHO for drinking and irrigation water at most of the sampling sites. The HPI and HEI values also surpassed the maximum limit of the study sites. The highest HPI and HEI values were found at the Yam1site. Oral ingestion represented 99.55% and 97.85% of CDItotal (CDIingestion + CDIdermal contact) in adults and children, respectively. The mean CDItotal and the noncarcinogenic risk values were found in the order of Fe > Mn > Cu > Zn > Cr in both ages. CDI, HQ, HI, and THI scores were higher in children. The HIoral and THI values were also higher than 1 in both ages except in DK 2, Sour 1, and Sour 2 sites. However, the HQdermal level was higher than 1 only for Cr in children. The ELCR obtained also indicated a high carcinogenic risk of Cr (0.75 ± 0.44 and 1.15 ± 0.66 in adults and children, respectively). In general, most of the study sites had heavy metal pollution levels that exceeded the maximum allowed limit. Therefore, effective management of sources of pollution and continuous monitoring of river quality to minimize health risks are very important.